Pengaruh pelatihan, disiplin kerja dan komunikasi terhadap kinerja karyawan pada PT.Sanytoga Gemilang - Agung Anggoro, Muhammad; Sibagariang, Overagus (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
Abstract Employee Performance is the level of success of employees in carrying out their duties. Factors affecting employee performance are training, work discipline, and communication. Training is a process to maintain or improve employee skills to produce effective work. The method of the research uses a quantitative approach, the research type is descriptive quantitative. Data collected by interviews, questionnaires, and study documentation. Data analysis used multiple linear regression. The population is all employees of the company that totaling 186 people. Sample determined by the Slovin formula, with 127 samples and for the validity test, 30 respondents were taken outside of the sample. The results showed that training, discipline, and communication simultaneously and partially had a positive and significant effect on employee performance with a determinant coefficient of 92.9% and the remaining 7.1% was influenced by other factors. The conclusion of this research is that simultaneously and partially training, discipline, and communication have a significant effect on the performance of the employees of PT Sany Toga Gemilang. Keywords: Training, Discipline, Communication, Performance